Circulating microRNAs in breast cancer and healthy subjects - Zhu, Weizhu; Qin, Wenyi; Atasoy, Ulus; Sauter, Edward R (BMC research notes, 2009)
It has been demonstrated that extracellular mRNA can be detected in the circulation. Our hypothesis was that circulating miRNAs are also present and differentially expressed in the serum of breast cancer patients compared to controls. We measured miRNA in the serum of samples with and without the addition of miRNA prior to analysis. To test our RNA extraction efficiency, we spiked-in serial dilutions of single-strand C elegens miR-39 (cel-miR-39) and human miR-145 (has-miR-145) into goat serum and a 10 year old human serum specimen. We next analyzed miR-16, -145, and -155 in archived serum specimens from 21 participants, 13 of whom did and 8 of whom did not have breast cancer. We were able to detect the miRNAs from all the serum samples to which the miRNAs had been added. We were also able to detect endogenous miR-16, -145, and -155 in all serum samples. While the expression of all three miRNAs was similar in samples from healthy women compared to those with breast cancer, women with progesterone receptor (PR, p = 0.016) positive tumors had higher miR-155 expression than tumors that were negative for these receptors. 1) RNA species can be detected in archived serum; 2) miR-155 may be differentially expressed in the serum of women with hormone sensitive compared to women with hormone insensitive breast cancer. Screening serum for miRNAs that predict the presence of breast cancer is feasible, and may be useful for breast cancer detection.